2019
DOI: 10.3847/2041-8213/ab4b56
|View full text |Cite
|
Sign up to set email alerts
|

The First Detection of a Low-frequency Turnover in Nonthermal Emission from the Jet of a Young Star

Abstract: Radio emission in jets from young stellar objects (YSOs) in the form of nonthermal emission has been seen toward several YSOs. Thought to be synchrotron emission from strong shocks in the jet, it could provide valuable information about the magnetic field in the jet. Here we report on the detection of synchrotron emission in two emission knots in the jet of the low-mass YSO DG Tau A at 152 MHz using the Low-Frequency Array (LOFAR), the first time nonthermal emission has been observed in a YSO jet at such low f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(57 reference statements)
2
17
0
Order By: Relevance
“…The detection of such a low frequency turn-over would be important for an increased understanding of the source structure and, possibly, its formation. Feeney-Johansson et al (2019) established that a low-frequency turn-over is present in one, and possibly both, of the synchrotron emission regions in DG Tau. The implications for the strength of the magnetic field depend on the mechanism causing the turn-over.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The detection of such a low frequency turn-over would be important for an increased understanding of the source structure and, possibly, its formation. Feeney-Johansson et al (2019) established that a low-frequency turn-over is present in one, and possibly both, of the synchrotron emission regions in DG Tau. The implications for the strength of the magnetic field depend on the mechanism causing the turn-over.…”
Section: Introductionmentioning
confidence: 95%
“…It was shown in the previous section that observation of the synchrotron self-absorption frequency provides an estimate of the emitting surface (equation 15). In addition to synchrotron self-absorption, the most likely mechanisms to cause a low frequency turn-over are free-free absorption and the Razin effect (Feeney-Johansson et al 2019). The aim in this section is to deduce constraints on the size of the synchrotron source that can be obtained from either of these mechanisms.…”
Section: Implications Of a Low Frequency Turn-over In A Synchrotron S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to inaccuracies in LOFAR beam models (Van Weeren et al 2016;Shimwell et al 2019), the derived flux density scale is often not accurate. To account for this, in Feeney-Johansson et al (2019) the integrated flux densities of several compact bright sources in the field were compared with their 1 https://github.com/lofar-astron/prefactor 2 https://github.com/lofar-astron/factor values in the TIFR GMRT Sky Survey (TGSS; Intema et al 2017). It was found that the average ratio of TGSS flux densities to LOFAR flux densities was 0.83 ± 0.17.…”
Section: Lofar Observationsmentioning
confidence: 99%
“…Radiative shocks are not efficient particle accelerators, however, there is evidence of nonthermal emission. Synchrotron radio emission has been detected both in protostellar jets (e.g., Carrasco-González et al 2010;Feeney-Johansson et al 2019) and novae (e.g., Vlasov et al 2016), whereas gamma-rays have only been detected in the latter (Ackermann et al 2014a). Accelerating synchrotron radio emitting electrons is possible for almost any kind of shock.…”
Section: Introductionmentioning
confidence: 99%